Disrupted Plurality in Agricultural Sustainability Narratives Worldwide - Maharani, Intan Mega; Rosyita, Dita; Astaman, Putra; Hikmah, Aulia Nurul; Widayanti, Annisa Vira (Tarjih : Agribusiness Development Journal, 2025)
Sustainability has become central in global agricultural research, especially since the SDGs’ adoption in 2015. However, technocratic and market-based narratives still dominate, sidelining equity-based and community-rooted knowledge, particularly from developing countries. This study analyzes 411 Scopus-indexed articles (1990–2025) using bibliometric methods. Focusing on co-authorship, corresponding authorship, and citation networks, the analysis compares the pre-SDG (1990–2014) and SDG (2015–2025) periods. The findings show that, despite expanded international collaboration and increased participation from the Global South in the SDG era, epistemic leadership and citation visibility remain highly concentrated within Global North institutions. While Global South contributions have grown, their largely peripheral positioning limits their influence over dominant sustainability framings. These results indicate that sustainability framing in agricultural research is not conceptually neutral but structurally conditioned by unequal knowledge systems. Addressing such epistemic asymmetries is therefore essential for enabling more plural and context-sensitive sustainability discourses.